The Impact of Economic And Social Factors on Demand For Health Insurance: Case Study of Metropolitan Cities - Rani Handayani; Nurmiati Nurmiati; Susanti Susanti; Erlina Puspitaloka Mahadewi (CV. Inara, 2025)
The present study reports the comprehensive study on socioeconomic aspects of health refer to social and economic factors that influence the living conditions of a person, family, or society. Health insurance is a health financing guarantee that needs to be chosen to face health risks and increasingly expensive medical costs. Socioeconomic status is related to the level of ability a person has in purchasing health services. This research aims to determine the influence of socio-economic factors on the demand for health insurance in metropolitan cities. This research uses a literature review research method which is part of qualitative research, which is related to the research subject. The results of this study show that the impact of economic and social factors or socio-economic factors can influence the demand for health insurance in metropolitan cities. The health insurance has a positive impact, there are still challenges related to the low penetration of health insurance among Indonesian people, especially in remote and rural areas. Apart from that, inadequate health insurance protection and a lack of understanding of the benefits of health insurance itself are also things that need attention. The role of the government, financial institutions and the insurance industry in increasing awareness, accessibility and reliability of health insurance products in the future will be key in strengthening the positive social and economic impact of health insurance in Indonesia.